Comparative phylogenetic and expression analysis of small GTPases families in legume and non-legume plants - Flores, Ana Claudia (2018)
Background: Small monomeric GTPases act as molecular switches in several processes that involve polar cell growth, participating mainly in vesicle trafficking and cytoskeleton rearrangements. This gene superfamily has largely expanded in plants through evolution as compared with other Kingdoms, leading to the suggestion that members of each subfamily might have acquired new functions associated to plant-specific processes. Legume plants engage in a nitrogen-fixing symbiotic interaction with rhizobia in a process that involves polar growth processes associated with the infection throughout the root hair. To get insight into the evolution of small GTPases associated with this process, we use a comparative genomic approach to establish differences in the Ras GTPase superfamily between legume and nonlegume plants. Results: Phylogenetic analyses did not show clear differences in the organization of the different subfamilies of small GTPases between plants that engage or not in nodule symbiosis. Protein alignments revealed a strong conservation at the sequence level of small GTPases previously linked to nodulation by functional genetics. Interestingly, one Rab and three Rop proteins showed conserved amino acid substitutions in legumes, but these changes do not alter the predicted conformational structure of these proteins. Although the steady-state levels of most small GTPases do not change in response to rhizobia, we identified a subset of Rab, Rop and Arf genes whose transcript levels are modulated during the symbiotic interaction, including their spatial distribution along the indeterminate nodule. Conclusions: This study provides a comprehensive study of the small GTPase superfamily in several plant species. The genetic program associated to root nodule symbiosis includes small GTPases to fulfill specific functions during infection and formation of the symbiosomes. These GTPases seems to have been recruited from members that were already present in common ancestors with plants as distant as monocots since we failed to detect asymmetric evolution in any of the subfamily trees. Expression analyses identified a number of legume members that can have undergone neo- or sub-functionalization associated to the spatio-temporal transcriptional control during the onset of the symbiotic interaction.